2004
DOI: 10.1158/1078-0432.ccr-03-0662
|View full text |Cite
|
Sign up to set email alerts
|

pRb2/p130, Vascular Endothelial Growth Factor, p27(KIP1), and Proliferating Cell Nuclear Antigen Expression in Hepatocellular Carcinoma

Abstract: Hepatocarcinoma (HCC) is the fifth most common cancer, with more than one million fatalities occurring annually worldwide. Multiple risk factors are associated with HCC disease etiology, the highest incidence being in patients with chronic hepatitis B virus and hepatitis C virus, although other factors such as genetic makeup and environmental exposure are involved. Multiple genetic alterations including the activation of oncogenes and inactivation of tumor suppressor genes are required for malignancy in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 40 publications
3
27
0
1
Order By: Relevance
“…However, altered pRB expression appears to be significantly related to poor grade (moderately vs well differentiated, Po0.01; poorly vs moderately differentiated, Po0.001) and advanced stage (Po0.001) (Hui et al, 1999). Moreover, we recently observed that pRb2/p130 expression in HCC is independent from tumor stage, suggesting its possible role as independent prognostic molecular biomarkers (Claudio et al, 2004).…”
Section: Gastrointestinal Cancermentioning
confidence: 87%
“…However, altered pRB expression appears to be significantly related to poor grade (moderately vs well differentiated, Po0.01; poorly vs moderately differentiated, Po0.001) and advanced stage (Po0.001) (Hui et al, 1999). Moreover, we recently observed that pRb2/p130 expression in HCC is independent from tumor stage, suggesting its possible role as independent prognostic molecular biomarkers (Claudio et al, 2004).…”
Section: Gastrointestinal Cancermentioning
confidence: 87%
“…Another study of 20 patients with HCC confirmed that higher VEGF expression was associated with a lower median survival. 42 Moreover, other studies have shown that expression of VEGF in HCC was correlated with the probability of recurrence after tumor resection or ablation. [43][44][45][46] Collectively, these findings suggest that tissue VEGF expression in HCC may indicate more advanced disease and reduced median survival.…”
Section: Molecular Interactions With Vegfmentioning
confidence: 98%
“…12 Additionally, we have demonstrated that pRb2/p130 is inversely correlated with VEGF expression and tumor aggressiveness (p < 0.05) in p27(KIP1)-negative hepatocarcinoma (HCC) patients. 18 In this recent study it was demonstrated that pRb2/p130 and VEGF expression are independent from tumor staging, suggesting their possible role as independent prognostic molecular biomarkers in HCC. Together, these data led us to investigate the expression levels of pRb2/p130 and VEGF in endometrial carcinoma in relation to histopathologic tumor grade in a cohort of 50 patients.…”
Section: Introductionmentioning
confidence: 94%
“…12 Additionally, these clinical data are in agreement with recent studies in which we showed that VEGF and pRb2/p130 are inversely correlated in hepatocarcinoma (HCC). 18 In this study, we evaluated the correlation differences between the FIGO grading system or the binary architectural grading system and the expression levels of pRb2/p130 and VEGF in predicting the progression of endometrial carcinogenesis. The present study was conducted in 50 cases of endometrial carcinomas.…”
mentioning
confidence: 99%